161k views
4 votes
How can I simplify the expression with rational exponents and radicals (x^2y)^3 2^√y^4.

How can I simplify the expression with rational exponents and radicals (x^2y)^3 2^√y-example-1

1 Answer

4 votes

We have


(x^2y)^3\sqrt[]{y^4}

we will use the next formulas in we can simplify the expression


\sqrt[m]{x^n}=x^{(n)/(m)}
(x^m)^n=x^(m\cdot n)
x^m\cdot x^n=x^(m+n)

so we can simplify the expression as


(x^2y)^3\sqrt[]{y^4}=x^(3\cdot2)y^(3\cdot1)(y^{(4)/(2)})=x^6y^3y^2=x^6y^(3+5)=x^6y^5

the expression simplified is


(x^2y)^3\sqrt[]{y^4}=x^6y^5

User Epifanio
by
5.0k points